The Innovation Process In Distance Higher Education - dos Santos, Tales Ramos Monteiro (Seven Editora, 2023)
The innovation process takes place from its implementation or restructuring according to the institution’s vision. Innovation is the ability to transform an idea, product, or service, according to Carreteiro (2009). Starting from the premise that Distance Education aims at the transformation of the individual, it is closely related to communicational technological advances, which is a process of constant innovation. The article is bibliographical research and is justified by the significant growth of this teaching modality in the country. It aimed to understand what innovation is in the context of distance higher education. The article is divided into 04 parts: a brief history of Distance Education, innovation, innovation strategies, and innovation as a business model. It is concluded that innovation must make use of strategies that dialogue with the entire organization to achieve the desired results. For this, it is necessary to review paradigms and that all those involved seek innovation continuously and procedurally under the organization’s mission. DOI: https://doi.org/10.56238/methofocusinterv1-037